Young emerging adults' graduateness and career adaptability: Exploring the moderating role of self-esteem. Issue 1 (29th February 2016) - Ismail, Sadika; Ferreira, Nadia; Coetzee, Melinde
Abstract : This study investigated the moderating role of self-esteem on young emerging adults' in their school-to-work transition phase of graduateness skills and career adaptability. A non-probability convenience sample ( n =332) of undergraduate black (98.5%) and female (62%) young emerging adults (18–29 years) at a Further Education and Training (FET) college in South Africa participated in the study. Participants completed the Culture Free Self-esteem Inventory for Adults (CFSEI 2-AD, Battle, 1992 ), the Graduateness Skills and Attributes Scale (GSAS, Coetzee, 2010 ) and the Career Adapt-abilities Scale (CAAS, Savickas & Porfeli, 2012 ). Hierarchical moderated regression analysis indicated significant interaction effects between self-esteem and overall graduateness, lifelong learning and global/moral citizenship skills and attributes in moderating overall career adaptability. The relationship between the participants' graduateness skills and attributes (overall graduateness, global/moral citizenship, and lifelong learning) and their career adaptability was significantly stronger when their self-esteem was high than when their self-esteem was low. The finding suggests self-esteem to influence self-perceived graduateness skills and career adaptability in emerging adults.